Multinucleation in Day Two Embryos Is Not Associated with Multinucleation in Sibling Embryos After Freezing and Thawing - J Seikkula; P Polo-Kantola; H Mankonen; H Mankonen; L Anttila; V Jokimaa (JRI, 2020)
Background: Multinucleated embryos exhibit impaired implantation potential, but whether the presence of multinucleated embryos in an embryo cohort reflects the quality of the entire cohort is controversial. No data exists on multinucleation rate among frozen-thawed embryos. Methods: De novo multinucleation and the number of multinucleated embryos on day two of embryo culture before freezing (D2) (n=415), at thawing (D2t) (n=320) and after an overnight culture after thawing (D3t) (n=265) was recorded. Associations between multinucleation before and after cryopreservation, female age and ovarian sensitivity to hormonal stimulation were assessed.  Results: The occurrence of at least one multinucleated embryo per embryo cohort was 62.4% on D2, 16.3% on D2t and 31.7% on D3t. The presence of multinucleated embryos prior to freezing was not associated with de novo multinucleation during post-thaw culture (p=0.845). On D2, multinucleation was high in young women, irrespective of the number of collected oocytes (p=0.702). In older age groups, multinucleation was highest if >17 oocytes were obtained (p<0.001) and the odds for multinucleation was the lowest if the consumption of recombinant follicle-stimulating hormone was >238 IU/oocyte (In the age group of 30–35 years OR 0.25 [0.13–0.47], and the age group of 36–40 years OR 0.35 [0.20–0.63]. Conclusion: Multinucleation is commonly seen in embryos and good-quality day two embryo cohorts before freezing. The presence of multinucleated embryos prior to freezing does not illustrate multinucleation in sibling embryos after thawing. Embryo multinucleation is associated with factors related to good prognosis in assisted reproduction treatments.